El aprendizaje significativo como estrategia didáctica para mejorar el proceso de enseñanza-aprendizaje de los estudiantes del séptimo año de educación básica en la unidad educativa fiscal”15 de noviembre” del cantón Quevedo Provincia de los Ríos año lectivo 2015. - Molina Acurio, Gladys Marlene (2015)
The importance of this research thesis is focused on meaningful learning for improving the teaching-learning process of the students, that contributes to the solution of the problem, in the same way with the development of the research a great contribution is being given to the teaching-learning process through the recommendation of alternatives that offers new pedagogical processes in the educational system. The main objective is to make research more relevant to the theoretical framework, is an integrated approach systematic to carry out an activity that must be met in a given time, for which arises objectives in terms considered diverse alternatives of action, a form of quantitative, documented, field research, descriptive and feasible project aimed at teachers and students of the educational Unit Prosecutor "15 November" beneficiaries of the project variables identified for the training of students, which helps the academic welfare of society and the population. And the project guide is a clear tool that helps the process of teaching and learning in the academic process.